Update on pharmacotherapies for cholestatic liver disease. Issue 1 (21st December 2016) - Ali, Ahmad H.; Tabibian, James H.; Lindor, Keith D.
Abstract : Cholestatic liver diseases are conditions with impaired bile formation and/or flow due to genetic, immunologic, environmental, or other causes. Unless successfully treated, this can lead to chronic liver injury and end‐stage liver disease. Primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) embody the most prominent adult cholestatic liver diseases with regard to incidence, morbidity, and mortality. A considerable proportion of patients with PBC and PSC experience progressive liver disease and ultimately liver‐related death due to a paucity of effective pharmacotherapy; however, novel pharmacologic developments offer substantial promise in this regard. Here, we provide a brief review and update on current and emerging pharmacotherapies for PBC and PSC. (Hepatology Communications 2017;1:7–17)